2011
DOI: 10.1097/jnr.0b013e318236d03f
|View full text |Cite
|
Sign up to set email alerts
|

A Computer Literacy Scale for Newly Enrolled Nursing College Students

Abstract: With increasing use of information technology applications, courses related to hardware topic should be increased to improve nurse problem-solving abilities. This study recommends that emphases on word processing and network-related topics may be reduced in favor of an increased emphasis on database, statistical software, hospital information systems, and information ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The US Department of Education defines computer literacy as “computer skills and ability to use technology to improve learning, productivity, and performance” [40]. However, the definition of computer literacy changes as technology evolves [49] and several studies have included “using networked communication” as a component of computer literacy [50-52]. Use of social networking sites (SNS), whether by mobile device or desktop computer, requires a certain level of computer literacy as a foundation [53].…”
Section: Methodsmentioning
confidence: 99%
“…The US Department of Education defines computer literacy as “computer skills and ability to use technology to improve learning, productivity, and performance” [40]. However, the definition of computer literacy changes as technology evolves [49] and several studies have included “using networked communication” as a component of computer literacy [50-52]. Use of social networking sites (SNS), whether by mobile device or desktop computer, requires a certain level of computer literacy as a foundation [53].…”
Section: Methodsmentioning
confidence: 99%
“…However, the definition of computer literacy changes with the technology evolution [29], and several recent studies have demonstrated the positive relationship between use of social networking sites and computer literacy [30,31]. …”
Section: Methodsmentioning
confidence: 99%
“…Availability of computers have resulted in our ability to rapidly and effectively,retrieve,analyze, share, and store large volumes of information related to patient care and for teaching-learning process in teaching hospitals ( Masood, Khan, & Waheed, 2010 ) and they noted that computer skills are vital for medical practitioners of the futures. The increasing use of IT in healthcare to posit that healthcare services efficacy and efficiency can be improved through informatics technology and systems and,thus, provide higher–quality healthcare for patients ( Tung-Cheng, 2011 ).…”
Section: Introductionmentioning
confidence: 99%